2022
DOI: 10.1002/jocb.536
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive–Creative Profiles of Insightful Problem Solvers: A Person‐Centered Insight Study

Abstract: This study aimed to portray insightful problem solvers. Participants solved classic insight problems and rebuses and completed cognitive and creativity tasks. Grouping the participants based on their success in solving insight problems of different modalities revealed that 95% of the spatial problem solvers succeeded in solving verbal ones (spatial verbal solvers) but not vice versa. Verbal problem solvers were not necessarily able to solve spatial ones. A latent class analysis (LCA) based on relationships amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…A new question may arise as to whether insight is rare for other than process-related factors? In our previous study, we attempted to answer this question by addressing IP solving from a person-centered perspective (Salmon-Mordekovich & Leikin, 2022 ). Results showed that experts on IP solving, constituting 12% of the sample, had unique characteristics related to creative and intellectual competencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new question may arise as to whether insight is rare for other than process-related factors? In our previous study, we attempted to answer this question by addressing IP solving from a person-centered perspective (Salmon-Mordekovich & Leikin, 2022 ). Results showed that experts on IP solving, constituting 12% of the sample, had unique characteristics related to creative and intellectual competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Inductive thinking test. Raven’s advanced progressive matrices (RAPM, Raven et al, 1996 ) (shortened version, Salmon-Mordekovich & Leikin, 2022 ) comprises a series of abstract figures arranged in a 3 × 3 matrix in which one figure is missing. The task is to discover rules by which to identify which one of eight alternatives completes the matrix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation